2020
DOI: 10.1155/2020/7045217
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cytology of Samples with Ureaplasma urealyticum, Ureaplasma parvum, Chlamydia trachomatis, Trichomonas vaginalis, Mycoplasma hominis, and Neisseria gonorrhoeae Detected by Multiplex PCR

Abstract: Introduction. Despite increasing application of molecular diagnostic methods for the detection of sexually transmitted infections, the cytological findings in pap smears of patients with pathogens that can be identified only by PCR are not yet well described. The aim of this study was to describe the most common cytological features in cervical pap smears of patients with Chlamydia trachomatis, Neisseria gonorrhoeae, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…Additionally, we found that U. parvum was the most frequent bacterial agent detected (n = 125/283, 44.2%). Our results are similar to obtained in a recent study, which U. parvum was the most prevalent mycoplasma in the cervix (Carneiro et al, 2020). However, for these authors, U. parvum, M. hominis and U. urealyticum were detected at much lower rates (14.9%, 8.5% and 4.2%, respectively) than in our study, and M. genitalium was also not detected.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, we found that U. parvum was the most frequent bacterial agent detected (n = 125/283, 44.2%). Our results are similar to obtained in a recent study, which U. parvum was the most prevalent mycoplasma in the cervix (Carneiro et al, 2020). However, for these authors, U. parvum, M. hominis and U. urealyticum were detected at much lower rates (14.9%, 8.5% and 4.2%, respectively) than in our study, and M. genitalium was also not detected.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed an overall rate of STI-positive cases (46.4%), higher in women aged 41-50 years, a frequent percentage described in a diversity of populations [17][18][19]. In this sense, Kim et al demonstrated rates of STI-positive status of 49.2% and showed a peak distribution in those 40-49 years old, which highlights comparable results with our study population [19].…”
Section: Discussionsupporting
confidence: 89%
“…Coinfections were not the most prevalent cases, with 12.7%, with similar results (12.8%) in Cervical Cytology of Samples using homolog PCR techniques [17]. Another common finding was the coinfections: Candida spp.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A colonização do trato genitourinário por micoplasmas genitais é frequente em mulheres saudáveis e sintomáticas (HORNER et al, 2018) Comparando os nossos resultados com as análises feitas em estudos brasileiros com mulheres não gestantes assintomáticas, as prevalências de Mh variaram de 0,8% -11,3% e para Ureaplasma spp. as taxas foram de 0,94% -14,9% (CARNEIRO et al, 2020;CHRISTOFOLINI et al, 2012;LIMA et al, 2018). Já em artigos realizados com populações sintomáticas, a prevalência de Mh apresentou taxas de 21,9 -31,8% e Ureaplasma spp.…”
Section: Prevalência E Fatores De Risco Associados à Infecção Por Micoplasma Genitalunclassified